(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: This study aimed to describe the prevalence of premenstrual syndrome (PMS) and analyze its relationship with some risk factors among female students at Hanoi Medical University in 2022. Subject and method: A cross-sectional descriptive study in all majors from the first to the sixth year of Hanoi Medical University. Results: Out of 412 study subjects, 69.9% of students had no PMS or mild PMS; 30.1% had moderate to severe PMS. Fatigue/lack of energy (89.3%) and anxiety/tension (78.2%) were the most common symptoms. Bachelor curriculum, dysmenorrhea, the amount of menstrual bleeding and total sedentary time were the associated factors with the higher severity of PMS (p<0.05). Conclusion: PMS was a common problem among female medical students. There is a need for screening and early detection of premenstrual syndrome, then having a plan to manage risk factors to improve the severity of this syndrome.